Metathesis with alkanes elucidating reaction pathways - Díaz, Estefanía; Restrepo, Albeiro; Solans Monfort, Xavi (2021)
Acquire a molecular understanding of the active sitesand proper reaction mechanism of alkane metathesiswith silica-supported tantalum single-site catalysts.